Ogilvie syndrome secondary due to underlying hypokalaemia and anticholinergics: case report and brief review of the literature - Iftikhar, Namirah; Muhammad Osama Rehman Khalid,; Uzma Ghori, (Journal of the Pakistan Medical Association, 2023)
Ogilvie's syndrome is a rare but potentially life-threatening condition characterised by massive dilation of the colon without a mechanical obstruction. It typically affects older adults and those with underlying medical conditions, such as neurological or cardiovascular diseases, and may result in severe complications such as perforation or sepsis. Diagnosis is based on clinical presentation and radiological studies, and treatment involves a combination of conservative measures, such as bowel rest and pharmacological agents, and interventional procedures, such as endoscopic decompression or surgery. Here we present the case of a 67 year old male who presented with Ogilvie’s syndrome after changes in his antipsychotic medications. He was given laxatives which led to persistent hypokalemia contributing to worsening distention. This case report highlights the important aspects in management such as cautious use of secretory laxatives (causing worsening Hypokalemia) and combination of motility agents in pseudo colonic obstruction.